Eficiência do uso da agricultura de precisão em áreas de abertura - Wierzbicki, Rafaella Gai dos Santos (2023)
Precision Agriculture (PA) techniques are used to replace traditional technologies that treat the crop as they work and apply inputs uniformly at fixed rates. The replacement of conventional fertilizer application techniques (uniform application) by precision agricultural techniques (variable fertilizer application) aims to achieve one of the following results: a) cost reduction by reducing the use of fertilizers; b) increase in agricultural productivity through more efficient application of fertilizers; and c) reduction of area heterogeneity. However, there are still many doubts about the effectiveness of precision agriculture, especially when it comes to open areas. Thus, the objective of this work was to study whether the application of AP and the use of variable rates is really an effective technique in these areas of the first year of agricultural cultivation, analyzing the conditions to increase the efficiency in the use of inputs and the productivity of the cultures. The importance of crop evolution in the results of the uniform application of inputs was also highlighted in the structure, due to the important impact it has on results. We conclude that, in general, contracting PA services and applying fertilizers at variable rates in opening areas is not part of the set of techniques immediately adopted, since the levels of nutrients observed in these areas are low and the amount of fertilizer applied at the rate fixed and high will have the productive response of the crop.